JURASSIC SEDIMENTARY AND TECTONIC PROCESSES AT MONTAGNA GRANDE (TRAPANESE DOMAIN, WESTERN SICILY, ITALY) - LUCA MARTIRE; GIULIO PAVIA (Rivista Italiana di Paleontologia e Stratigrafia, 2004)
The Rosso Ammonitico of the Montagna Grande area is very interesting because of the great diversification in facies and thickness in three very closely situated sections. The Jurassic succession in this area is that typical of the Trapanese Domain. It starts with a thick pile of platform limestones (Inici Formation: Hettangian - Sinemurian) that are overlain by typically condensed and commonly nodular pelagic limestones (Rosso Ammonitico: Middle Jurassic - lowermost Cretaceous). The good exposure of this succession in active quarries allows observation of sedimentological and palaeontological details and to improve the understanding of the Jurassic tectono-sedimentary evolution. The Rocca chi Parra quarry shows a stepped surface, with a relief of some metres, incised in the Inici Formation. It is covered by lenticular or wedge-shaped lithosomes a few metres-thick of highly condensed Rosso Ammonitico. It is interpreted as a slide scar along which a thin but extensive block of lithified platform limestones was detached and slid downslope. The Poggio Roccione quarry shows neptunian sills and collapse structures in the middle part of the Rosso Ammonitico that on the whole is thicker (about 12 m) than at Rocca chi Parra. They indicate sea-floor instability probably due to seismic shocks with brittle to plastic behaviour of sediments depending on their coherence. The Montagna Grande outcrop shows an even thicker succession which includes a wedge of cherty limestones about 10 m thick intercalated between a lower and an upper Rosso Ammonitico calcareous unit. The features described in these three sections document a highly irregular sea-floor topography which in turn was controlled by several phases of extensional tectonics during Mid and Late Jurassic pelagic sedimentation. Structurally higher sectors closer to fault scarps were affected by a very condensed sedimentation, the opening of subvertical dykes and the triggering of large slides. Structurally lower sectors allowed preservation of thicker successions that were affected by gravitationally-induced soft to hard sediment deformation when tectonics resulted in an oversteepening of the slope.